Christianity and black masculinity in James Baldwin’s Blues for Mister Charlie and August Wilson’s Joe Turner’s come and gone = Cristianismo e masculinidade em Blues for Mister Charlie, de James Baldwin e Joe Turner’s come and gone, de August Wilson - Laranjeira, Delzi Alves (Numen, 2013)
Religion works as a modeling system, that is, it rules and orients a notion of reality and how to act according to its truths and assumptions. In William Baldwin’s Blues for Mister Charlie and August Wilson’s Joe Turner’s come and gone, the main characters undergo a deep identity crisis, emphasized by the confrontation of Christian premises strongly taken for granted with new ways of conceiving and realizing spirituality. By analyzing the way this crisis is established and solved within the plays it is possible to identify a criticism to the notion of black masculinity embedded in a Christian perspective.